Native Missing Persons Cases Will Not be Solved by Police Alone: The Case for “Missing Persons Advocates” - Gilbert, Sheena L. (Journal of interpersonal violence, 2023)
This study explored the potential role of victim advocacy in Native American missing person cases. Interviews with 25 tribal and non-tribal victim/social service providers were conducted to assess their perspectives on the factors which make Native Americans vulnerable to going missing, the barriers and challenges regarding reporting and investigating missing persons, as well as how victim/social service providers might better support the families of missing persons. Findings suggest that advocates perceive that responding to and offering services for Native families who experience a missing loved one will be extremely difficult because of the intersection of isolation, poverty, and jurisdictional complexities among tribal lands, combined with social service providers and law enforcement officers’ lack of resources and training regarding cultural sensitivity. At the same time, advocates suggest that additional training and resources could help overcome many of these barriers and see a role for victim service providers in responding to missing and murdered Native American persons. Implications and suggestions for practice are discussed.